An investigation of the reactions of substituted homoallylic alcohols with various oxidation reagents - Servi, S; Acar, A (Molecular Diversity Preservation International, 2002)
Substituted homoallylic alcohols have been synthesised both by [2,3]-Wittig rearrangement of unsymmetrical bis-allylic ethers and reaction of alkenyl chloromethyl oxiranes with Mg/THF. These substrates were then oxidized using four different oxidants. When the substituted homoallylic alcohols were oxidized with pyridinium chlorochromate or zinc chlorochromate nonahydrate the corresponding carbonyl compounds were produced. The same substrates formed the corresponding allylic oxidation products together with epoxidation products when oxidized with t-BuOOH. When and t-BuOOH and catalytic amounts of OSO4 were used the allylic oxidation reaction was prevented and the only products formed were those in which the substituted double bond was epoxidized.
Keywords: substituted homoallylic alcohols; oxidation reagents; osmium tetroxide; t-butyl hydroperoxide